1968
DOI: 10.1002/pol.1968.150060109
|View full text |Cite
|
Sign up to set email alerts
|

Cyclopolymerization of diallylcyanamide

Abstract: A soluble polymer of cyclic structure has been obtained by radical polymerization of diallyleyanamide. A kinetic analysis of the polymerization indicated that the overall rate of the system is first‐order with respect to concentration of initiator and either first‐ or second‐order with respect to monomer concentration, depending on the solvent used. The molecular weight of the polymer is independent of the concentration of the initiator and the monomer. The intramolecular abstraction of hydrogen is proposed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1969
1969
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…perimental results as Taking into account the general sequence of reactions, initiation, propagation through cyclopo- [6][7][8][9][10][11][12] termination of a growing radical through a degradative chain transfer reaction 16,18 with PDP, and final termination of a growing cy-…”
Section: Effect Of Acid Strength and Ionic Strength On R Pmentioning
confidence: 99%
See 1 more Smart Citation
“…perimental results as Taking into account the general sequence of reactions, initiation, propagation through cyclopo- [6][7][8][9][10][11][12] termination of a growing radical through a degradative chain transfer reaction 16,18 with PDP, and final termination of a growing cy-…”
Section: Effect Of Acid Strength and Ionic Strength On R Pmentioning
confidence: 99%
“…a symmetrical nonconjugated divinyl monomer, has received recent attention because of the involvement of a novel propagation step known It is well known that thiocarboxylic acids exert an activating influence on peroxydisulfate in the as cyclopolymerization. [6][7][8][9][10][11][12] This prompted us to undertake the detailed kinetic and comparative initiation of vinyl polymerization reactions. [1][2][3] In recent years thiocarboxylic acids have been used study of polymerization of N,N-methylenebis-(acrylamide) initiated by PDP-TLA, PDP-TMA, as redox components with PDP as oxidant for the polymerization of monovinyl monomers.…”
Section: Introductionmentioning
confidence: 99%
“…15 In our recent study, we have demonstrated that polymerization of DAM in concentrated aqueous solutions by radical initiation gives a water-soluble homopolymer. 16 Not only quaternary diallyl ammonium monomers but also some other divinyl monomers such as diallyl sulfonamide 17 and dially cyanamide 18 can give cyclopolymers with similar structures.…”
Section: Introductionmentioning
confidence: 99%